Acute cardiovascular responses to a session of Manual Lymphatic Drainage - Plínio dos Santos Ramos; Isabelle Regina Moreira Marinho Cunha; Mariana Cristina Rachel; Priscilla Stephan Souza Pacca; Ana Paula Ferreira; Djalma Rabelo Ricardo
Introduction Manual Lymphatic Drainage (MLD) creates pressure differentials to promote the movement of lymph and interstitial fluid, for their relocation into the bloodstream and can thus act on the variables responsible for determining blood pressure (BP). Objective To investigate the behavior of hemodynamic parameters, such as BP and Heart Rate (HR) during and immediately after a session of MLD. Materials and methods 23 healthy young volunteers with a mean age of 22 ± 2.97 years (18-29), underwent a session of MLD and evaluation of systolic BP, diastolic BP and HR after 10 minutes of initial rest, at the end of the implementation of the protocol in SP, PP and after 15 minutes of final rest. Results No changes were found in systolic BP or diastolic BP before, during and immediately after the MLD session (p = 0.57, p = 0.20, respectively). There was increased heart rate after the final 15 minute rest when compared to the HR after MLD in SP (72 ± 1.9 vs. 76 ± 1.9, p = 0.002), however, without clinical relevance. Conclusion During a session of MLD with healthy young women, no significant hemodynamic changes occurred, demonstrating that this technique is safe from the cardiovascular point of view.